Strategi Majelis Taklim Al-Kamal Medan Dalam Meningkatkan Kualitas Sumber Daya Manusia dan Kurikulum - Nesa Tri Utami; Abdullah Habib Nasution; Ibnusyah Sitompul; Aisyah Ramadhani; Hendra Kurniawan (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This research discusses how the Medan Al-Kamal Taklim Council implements strategies to improve the quality of human resources (HR) and develop non-formal education curricula. The Taklim Council implements structured learning, trains ustadz/ustadzah, develops administrators, and actively involves the congregation in study activities. The curriculum is adapted to social conditions, technology and current challenges, including classical religious material, digital literacy, Islamic life skills and sharia entrepreneurship. Routine evaluation and understanding the needs of the congregation are part of the strategy to make learning more relevant and useful. The research results show that improving human resources and appropriate curriculum makes the congregation better understand religion, more skilled and more active in participating. In this way, the Al-Kamal Taklim Council is able to become a non-formal educational institution that is adaptive, productive and has a positive impact on the congregation and society. Keywords: Taklim Council, Human Resources, Curriculum, Non-formal Education, Da'wah Strategy